Design and Implementation of Lightweight Virtualization Using Docker Container in Distributing Web Application with Experimental Methods - Stefanus Eko Prasetyo (Universitas Medan Area, 2021)
The rapid development of website-based applications that can be accessed on various computer platforms and smart phones, causing the infrastructure of web application deployment, especially servers, is needed. This causes sometimes the organization needs to invest in a server. With virtualization, companies can create multiple servers on the same machine, and each server functions as an individual machine. Lightweight based virtualization or known as containers is an approach where the host operating system is shared with a virtual server which means that the parent kernel is shared with virtual servers or containers. The method used is an experimental method, this study measures the effect of a particular treatment on a variable with different treatments. Research variables carried out in the lightweight virtualization system research, including: throughput, Average Latency, response time and Dropped Request. The treatments in this study were tested with 100, 200, 250 and 300 connections simultaneously with 1000, 3000, 5000, 7000 requests.The server service design uses container-based virtualization for the webserver with 2.8 Ghz (4 core) Intel Core i7 processor specifications, 2 GB memory, 80 GB M2 SSD storage, and Gigabit Ethernet capable of handling 250 requests simultaneously, but cannot be accessed when handling 300 requests simultaneously.